Oriented inclusions of pyroxene, amphibole and rutile in garnet from the Lüliangshan garnet peridotite massif, North Qaidam UHPM belt, NW China: an electron backscatter diffraction study. (14th July 2016) - Xu, H. J.; Wu, Y.
Abstract: Oriented inclusions of clinopyroxene, orthopyroxene, sodic amphibole and rutile have been identified in garnet from the Lüliangshan garnet peridotite massif in the North Qaidam ultrahigh‐pressure metamorphic (UHPM) belt, northern Tibetan Plateau, NW China. Electron backscatter diffraction (EBSD) analyses demonstrate that nearly half of the measured intracrystalline clinopyroxene (8 out of 17) have topotactic crystallographic relationships with host garnet, that is, (100)Cpx //112Grt, (010)Cpx //110Grt and [001]Cpx //<111>Grt . One‐fifth of the oriented sodic amphibole (23 out of 110) inclusions of have topotactic crystallographic relationships with host garnet, that is, (010)Amp //112Grt, (100)Amp //110Grt and [001]Amp //<111>Grt . Over a third of rutile (36 out of 99) inclusions also show a close crystallographic orientation relationship with host garnet in that one <103>Rt and one <110>Rt parallel to two <111>Grt while the axes of [001]Rt exhibit small girdles centred the axes of <111>Grt . But, no 'well‐fit' crystallographic relationship was observed between orthopyroxene inclusions and host garnet. Considering a very long and complex history for the Lüliangshan garnet peridotite, we suggest that the low fit rates for these oriented minerals may result from several possible assumptions including different generations or multi‐stage formation mechanisms, heterogeneous nucleation and growth under non‐equilibrium conditions, and partial changes of initial crystallographic orientations of some inclusions. However, the residual quantitative 'well‐fit' crystallographic information is sufficient to indicate that the nucleation and growth of many pyroxene, amphibole and rutile are controlled by the lattice of the host garnet. The revealed close topotactic relationships accompanied by clear shape orientations provide quantitative microstructural evidence demonstrating a most likely exsolution/precipitate origin for at least some of the oriented phases of pyroxene, sodic amphibole and rutile from former majoritic garnet and support an ultra‐deep (>180 km depth) origin of the Lüliangshan garnet massif.